Binder jetting yttria stabilised zirconia ceramic with inorganic colloid as a binder. (17th November 2019) - Huang, Shuangjun; Ye, Chunsheng; Zhao, Huoping; Fan, Zitian; Wei, Qingsong
ABSTRACT: The new inorganic colloid is a particle-free decomposable binder that can solve the nozzle clogging problem and precipitate zirconia particle upon heating. The inorganic colloidal binder can be used as a binder precursor to replace commonly used PVP binder in printing ZrO2 ceramics parts using binder-jet technology. Green bodies were printed using inorganic colloid binders with different saturation level and PVP binder separately, then cured and sintered. The effects of binder saturation level and sintered temperature on the properties of the green and sintered bodies were investigated. After being deposited into the powder bed interstices and cured, the inorganic colloidal binder containing zirconium basic carbonate decomposes and forms ZrO2 ceramic particles that are filled the interstices and sintered to provide bonding strength to the printed parts. Samples with inorganic colloidal binder eventually perform better surface quality and denser sintered body than polymer binder when using same saturation ratio.